Mastering global business development and sales management - Cook, Thomas A., 1953- (Boca Raton, FL : CRC Press, 2021)
"This book focuses on the importance of companies and executives recognizing that their organization is sales driven, and that there is a definite pronounced connection between sales and all other aspects of how a company operates. It details the sales manager's role in developing sales personnel, delivering new business to the organization, and otherwise becoming a driving force for the overall prosperity of the company. The book differentiates itself by providing the essence of international sales management"--
OCLC-licensed vendor bibliographic record.
Keywords: Sales management; Marketing; Strategic planning; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Purchasing & Buying